Consulting project for the lubricants export department of Galp Energia: global market assessment and redefinition of the internationalization strategy - Couto, Beatriz de Melo Duarte Costa (2014)
The subsequent report is aimed at describing the group project conducted under the Management Consulting Field Labs initiative. It consisted of, as the name indicates, a consulting project completed by four NOVA SBE’s students for the Oil and Gas Company Galp energia (Galp)on its Lubricants Export Department(Export Department). The project’s main objective was to develop a global market assessment and redefine Galp’s Lubricants Export Department internalization strategy. In order to respond to the Company’s needs having in consideration the dimension of the scope, a high level approach was adopted. Furthermore, the close relationship with the client was critical in order to develop a project that matches the Export Department’s specific needs and therefore creating valuefor the client.